An interpretation of the Schrödinger equation in quantum mechanics from the control-theoretic point of view. (January 2019) - Ohsumi, Akira
Abstract: In this paper, for a given (time-dependent) Schrödinger equation in quantum mechanics, an interpretation of it is investigated from the perspective of stochastic control theory with the help of Nelson stochastic mechanics.